2008
DOI: 10.1038/jp.2008.66
|View full text |Cite
|
Sign up to set email alerts
|

Can magnetic resonance spectroscopy predict neurodevelopmental outcome in very low birth weight preterm infants?

Abstract: Objective: To determine if metabolite ratios at near-term age predict outcome in very low birth weight preterm infants at 18 to 24 months adjusted age.Study Design: Thirty-six infants (birth weight p1510 g, gestational age p32 weeks) were scanned at a postmenstrual age (PMA) of 35 to 43 weeks from July 2001 to September 2003. Multivoxel proton spectroscopic data were acquired and metabolite ratios were calculated in regions of the thalamus and basal ganglia. Bayley Scales of Infant Development were assessed be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
3
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 31 publications
2
22
3
1
Order By: Relevance
“…A decreased NAA/Cho ratio in the thalamus and white matter may indicate neurodevelopmental delay at 18 months corrected age. In contrast, Augustine et al reported that NAA/Cho, NAA/Cre and Cho/Cre ratios in the thalamus and basal ganglia were not predictive of Bayley scores at 18–24 months adjusted age 37. However, they used a larger voxel size than that in our study, which may have affected tissue specificity and resulted in regions of interest, including non-targeted tissues.…”
Section: Discussioncontrasting
confidence: 65%
“…A decreased NAA/Cho ratio in the thalamus and white matter may indicate neurodevelopmental delay at 18 months corrected age. In contrast, Augustine et al reported that NAA/Cho, NAA/Cre and Cho/Cre ratios in the thalamus and basal ganglia were not predictive of Bayley scores at 18–24 months adjusted age 37. However, they used a larger voxel size than that in our study, which may have affected tissue specificity and resulted in regions of interest, including non-targeted tissues.…”
Section: Discussioncontrasting
confidence: 65%
“…Three reported studies have examined the relationship of MRS cerebral metabolites and neurodevelopment in preterm infants. Augustine et al 32 did not identify any correlations between metabolite ratios in 36 very low birth weight preterm infants at the level of the basal ganglia and supraventricular level and Bayley mental and psychomotor scores at 18-24 months’ corrected age. Use of categorical rather than continuous outcomes and the small number of infants (n = 8) with abnormal neurodevelopmental outcomes likely resulted in reduced study power to find meaningful correlations.…”
Section: Discussionmentioning
confidence: 93%
“…At the same time, recent studies have documented associations between NAA/choline ratios in preterm neonates and later developmental outcome[6567] (but see also [68]). Although without outcome data, we cannot speculate on the clinical significance of the associations between white matter metabolism and thalamic volume observed in our study, these findings suggest that the observed association between NAA/choline and outcome might be further mediated by changes to the developing corticothalamic system.…”
Section: Discussionmentioning
confidence: 99%